2018
DOI: 10.1111/jfb.13755
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effect of a tidal, hydroelectric propeller turbine on the populations of three anadromous fish species

Abstract: Tidal hydroelectric power has been proposed as one potential solution for sustainable energy sources. The first tidal turbine in North America began continuous operation in the Annapolis River estuary (44 °45'N; 65° 29'W) in June, 1985. The machine is an axial-flow, hydraulic-lift propeller turbine, a type known to cause fish mortality. Anadromous populations of American shad Alosa sapidissima, striped bass Morone saxatilis and Atlantic sturgeon Acipenser oxyrinchus utilize the Annapolis River for spawning and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
(153 reference statements)
1
9
0
Order By: Relevance
“…Therefore, future work should be conducted to assess the fisheries' interactions with multiple devices, which has been highlighted as a future need and direction for hydrokinetic energy projects (Dadswell et al. 2018; Copping et al. 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, future work should be conducted to assess the fisheries' interactions with multiple devices, which has been highlighted as a future need and direction for hydrokinetic energy projects (Dadswell et al. 2018; Copping et al. 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this research did not monitor the presence of other anadromous and resident fish species that may encounter the turbine during other (unmonitored) periods of the year. Therefore, future work should be conducted to assess the fisheries' interactions with multiple devices, which has been highlighted as a future need and direction for hydrokinetic energy projects (Dadswell et al 2018;Copping et al 2021).…”
Section: Management Implicationsmentioning
confidence: 99%
“…This study is the first to provide baseline information concerning Atlantic sturgeons use of a future tidal energy site. This information is important to management because many sturgeons from endangered and threatened populations from Canada and the USA migrate through MP to enter MB to feed during 10–15 years of their juvenile life (Dadswell et al, 2016, 2018). Our results indicated that Atlantic sturgeon passed through the FORCE sites during May to Nov when they enter or leave MB, travelling pelagically in MP at a depth similar to proposed seabed mounted MHKs (Stokesbury et al, 2016; FORCE 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The information on diversity and abundance will be useful for future comparisons if there are changes in these characteristics of Minas Basin fishes caused either by tidal power development impact or exploitation. Also, the detailed length structure provided for each species will provide sufficient data for significant statistical comparisons in the future if the size structure of individual fish species is altered by propeller turbine mortality removing larger individuals (Dadswell et al 2018) or overexploitation. All these comparisons will be important for assessing any future impact of tidal energy development in the inner Bay of Fundy.…”
Section: Discussionmentioning
confidence: 99%